Про неперервність за параметром розв’язків крайових задач, тотальних щодо просторів C(n+r)[a,b] - Солдатов, В.О. (Український математичний журнал, 2015)
Рассмотрен широкий класс линейных краевых задач для систем обыкновенных дифференциальных уравнений — тотальные задачи относительно пространства C(n+r)[a,b], где n ∈ N, а r — порядок уравнений. Доказана теорема о существовании, единственности и непрерывной зависимости по параметру их решений в этом пространстве. We study a broad class of linear boundary-value problems for systems of ordinary differential equations, namely, the problems total with respect to the space C(n+r)[a,b], where n ∊ N and r is the order of the equations. For their solutions, we prove the theorem of existence, uniqueness, and continuous dependence on the parameter in this space.